Unusual Presentation of Cystic Lesions of the Jaws in a Patient with Pascual-Castroviejo Syndrome: A Case Report - Alejandro Cedeño; Gustavo Bustamante; Ejusmar Rivera; Ana Villarroel; Anixa Alvarez (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Pascual-Castroviejo syndrome or Cerebro-facial-thoracic dysplasia is an autosomal recessive inherited disorder characterized by mental retardation, typical facies, brachycephaly, calcified clinoid ligaments, and deformities of the superior rib arches. Its etiology is not entirely clear, but an association with a mutation in the TMC01 gene has been reported. On the other hand, the dentigerous cyst is the odontogenic cyst of the most common development in the jaws. It results from the accumulation of fluid between the reduced epithelium of the enamel and the crown. They are generally solitary lesions, rare to find them bilaterally and multiple, and not reported in the literature about this syndrome. This article presents a bilateral dentigerous cyst description in the mandible of a patient with Pascual-Castroviejo syndrome. A 14-year-old male patient with a diagnosis of cerebro-fascio-thoracic dysplasia (Pascual-Castroviejo syndrome), presenting a  bilateral lesion in the posterior mandible, with a year of evolution. An incisional biopsy was performed in the larger lesion, and the diagnosis was a dentigerous cyst. Subsequently, under general anesthesia, enucleation and curettage of the lesions associated with the second and third molars of the first, second, and third quadrant were performed, along with the involved teeth' extraction. Periodic postoperative controls were carried out, and after six months, there were no signs of recurrence. The appearance of cystic lesions of the jaws associated with the Pascual-Castroviejo syndrome is rare. Further genetic studies are crucial to determine the association between both entities.